APPROACHES TO STATIN THERAPY ADHERENCE IMPROVEMENT - S. A. Shalnova; V. N. Belov; M. N. Valiakhmetov; N. G. Veselovskaya; N. V. Voronina; A. V. Dmitriev; E. V. Efremova; L. О. Minushkina; A. М. Naydich; V. Yu. Pavlova; Ya. M. Pakhomov; A. Е. Rivin; et al. (Кардиоваскулярная терапия и профилактика)
Most cardiovascular diseases (CVD) are of atherosclerotic origin, and lipid disorders play significant role, setting up the cardiovascular continuum, together with other risk factors. It also known that decrease of low density lipoproteins cholesterol (CLDL) level leads to decreased occurrence of CVDs in primary and secondary prevention of the diseases. Statins, at the moment, are a standard of medical care. However, two problems remain on the way to cardiovascular risk reduction — insufficient statins prescription and low rate of archived target levels of cholesterol and CLDL. In the end of October 2017, by the initiative of Sandoz LLC, in Kazan an educational seminar was conducted, where the representatives from 12 regions discussed the issues on statin therapy adherence improvement. Seminar program included lectures, practical interactive events and general discussion. As a specifics of the seminar, the participants not only listened to lectures, but prepared proposals in interactive regimen, discussed them with the colleagues, presented and defended projects. So, every participant was merged into the problem and directly influenced the discussion. Among the participants were internists, cardiologists, neurologists. Seminar vector was directed to revealing and overcoming such barriers for statin adherence as the socalled barriers of consent, understanding and availability, that depend on clinician as well as patient and healthcare system. Also the issues were discussed on the Internet influence on “antistatin” behavior, that prefers “good” bioactive compounds for “vile” statins.